Hospital-Based Cancer Registries: Methodological Proposal for Correction of Lung Cancer Staging - Valerio, Tayná Sequeira (2023)
Introduction: A major challenge to utilize the registries and secondary databases is the quality of the data and the percentage of losses in strategic and necessary variables for better effectiveness of the database. Objective: To propose a correction method for the cancer staging variable of the Hospital-Based Cancer Registry (HBCR), to improve its completeness and quality. Method: HBCR-based descriptive analysis covering Brazil’s Federation Units from January 2013 to December 2019. Due to its high mortality in Brazil and worldwide, lung cancer was selected as case for database correction. The analyzes were performed with the software SAS Studio for statistical analyzes and the data were organized in Excel®. Results: The total number of cases registered at the HBCR was 86,026, and 32% the variable of interest, staging, were missed. At the end of the correction process, the missed data reached 9.8%, corresponding to a recovery of 22.2%. Conclusion: The proposed methodology is an advance for the correction of the HBCR database on the treatment of lung cancer, allowing a more extensive use, with better representativeness of different country regions, and potential utilization in other topographies.